DESIGN, MANUFACTURE, AND TEST of the STEWART-PLATFORM ROBOT - SANTOSO (NIM : 23107023); Pembimbing : Dr. Ir. Indrawanto, ANINDITO
In this thesis, the main topic is in designing control system and trajectory planning for Stewart-Platform robot. Stewart-Platform robot is a robot which has 6 prismatic actuator placed in parallel configuration. The robot in this thesis is designed using UPS (Universal-Prismatic-Spherical) configuration. The actuator used is a linear motor DC which used a screw mechanism to convert the rotary motion to linear motion. The problem with this type of robot lies in the control mechanism for the actuator. The control system must be able to control 6 actuators at the same time with small movement error. To address this problem, a control system based on state feedback with reduced order observer method is proposed. The state feedback with reduced order observer is composed by controller/control law part and observer part. The observer functioned in the measuring of the velocity and acceleration of the actuator, while the controller functioned in controlling the actuator so the actuator can move to the reference point in respond time as planned.